Peningkatan Kemampuan Guru Membuat Media Pembelajaran Berbasis Aplikasi Canva di Sekolah Penggerak - Nurhidayah, Nurhidayah; Arifin, Sartika; Latifa, Nur Fajriyah; Hikma, Hikma (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
The low ability of teachers to present digital-based learning makes teachers less than optimal in implementing learning with an independent curriculum. In implementing the independent curriculum, it is emphasized that learning resources are not only in the form of books, but can also use videos, interesting pictures, etc. so that they can increase children's motivation to participate in the learning process. Therefore, this PKM is implemented with the aim of improving teachers' ability to operate IT, especially in creating interesting learning media. The methods used in this PKM are lectures, simulations and workshops. The PKM implementation stage includes the first stage, namely coordinating and analyzing needs, the second stage is socializing Canva learning media, the third stage is training using the Canva application, and the fourth stage is evaluating teacher abilities. The expected result is that this activity can improve teachers' abilities in operating IT and can create interesting learning media. The result of implementing this community service is that there is an increase in teachers' ability to use the Canva application to create interactive and interesting learning media so that they can carry out fun and meaningful learning.